1991
DOI: 10.1038/354125a0
|View full text |Cite
|
Sign up to set email alerts
|

A novel highly unsaturated fatty acid moiety of lipo-oligosaccharide signals determines host specificity of Rhizobium

Abstract: In Rhizobium leguminosarum biovar viciae, the nodABC and nodFEL operons are involved in the production of lipo-oligosaccharide signals which mediate host specificity. The structure of these metabolites and those produced in nod mutants links the nodE and nodL genes to specific chemical features of the signal molecules. A nodE-determined, highly unsaturated fatty acid and a nodL-determined O-acetyl substituent are essential for the ability of the signals to induce nodule meristems on the host plant Vicia sativa. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
391
2
14

Year Published

1993
1993
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 518 publications
(423 citation statements)
references
References 31 publications
16
391
2
14
Order By: Relevance
“…Moreover, by showing that nodule meristematic centers can be detected during the very first hours following inoculation, before infection has progressed beyond the outermost plant cells, our results suggest that the meristem is induced at a distance (35,36). During the last decade, different groups have shown that nodulating rhizobia produce lipooligosaccharidic Nod factors (18,32), which are able to induce inner cortical cell divisions (32,36) and nodule development in alfalfa (36). More shown that A. caulinodans ORS571, the strain used as an inoculant in this study, also produces lipooligosaccharidic Nod factors (21).…”
Section: Discussionmentioning
confidence: 53%
“…Moreover, by showing that nodule meristematic centers can be detected during the very first hours following inoculation, before infection has progressed beyond the outermost plant cells, our results suggest that the meristem is induced at a distance (35,36). During the last decade, different groups have shown that nodulating rhizobia produce lipooligosaccharidic Nod factors (18,32), which are able to induce inner cortical cell divisions (32,36) and nodule development in alfalfa (36). More shown that A. caulinodans ORS571, the strain used as an inoculant in this study, also produces lipooligosaccharidic Nod factors (21).…”
Section: Discussionmentioning
confidence: 53%
“…Such contacts are usually between pairs of sideNodF directs the synthesis of a trans-2,trans-4,trans-6,cis-11-chain protons. However, the l~N-directed structure-determioctadecatetraenoic acid [6] which forms part of a host-specific nation strategy adopted here limits the NOEs primarily to lipo-chitin oligosaccharide signal [2]. Surprisingly, recent eviones involving at least one backbone amide proton or the dence even suggests that, besides a constitutive AcpP [39] and few contacts with sidechain -NH2s in glutamine, arginine the inducible NodF, there might be at least two additional and asparagine residues.…”
Section: ~ ] 34 Comparison Of the Structure With E Eoli Acpp Imentioning
confidence: 90%
“…Some elicitors have been identified in the Rhizobium-legume symbiosis (Spaink et al, 1991). Since the different signals (chemicals) involved have to be synthesized, the relevant metabolic processes should be stimulated after contact between host and fungus.…”
Section: Introductionmentioning
confidence: 99%